2022
DOI: 10.1007/s00062-022-01227-1
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography of the Spine

Abstract: The introduction of the first whole-body CT scanner in 1974 marked the beginning of cross-sectional spine imaging. In the last decades, the technological advancement, increasing availability and clinical success of CT led to a rapidly growing number of CT examinations, also of the spine. After initially being primarily used for trauma evaluation, new indications continued to emerge, such as assessment of vertebral fractures or degenerative spine disease, preoperative and postoperative evaluation, or CT-guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…In younger patients, for example, adhering to the ALARA principle, that is, to keep the radiation dose "as low as reasonably achievable," is a crucial aspect; however, images still need to be diagnostic to prevent repeated scanning. 5,24 Although dedicated ultra-low-dose scan protocols below 5 mGy were not in the scope of the present study, further patient studies are certainly warranted in that regard. As a major finding, our data suggest that solely computing CNR is no reliable indicator of perceptual image quality-a problem that has previously been described in the computer vision community.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In younger patients, for example, adhering to the ALARA principle, that is, to keep the radiation dose "as low as reasonably achievable," is a crucial aspect; however, images still need to be diagnostic to prevent repeated scanning. 5,24 Although dedicated ultra-low-dose scan protocols below 5 mGy were not in the scope of the present study, further patient studies are certainly warranted in that regard. As a major finding, our data suggest that solely computing CNR is no reliable indicator of perceptual image quality-a problem that has previously been described in the computer vision community.…”
Section: Discussionmentioning
confidence: 97%
“…3,4 Because physically active individuals are more often affected by spinal fractures, radiation protection and dose efficiency remain concerning issues when deciding on an appropriate scan protocol. 5,6 Finding the sweet spot between necessary radiation exposure and diagnostically acceptable image quality is a perennial challenge whenever technical advancements are introduced to clinical routine. 7,8 Most recently, the emergence of photon-counting CT (PCCT) systems has prompted a substantial increase in image quality for various diagnostic applications.…”
mentioning
confidence: 99%
“…Furthermore, we did not explicitly assess which parameter adjustments contributed the most to radiation dose reductions, and this may need to be solved primarily by phantom or cadaver studies in which more than one scan could be achieved, given that radiation protection is not an issue. However, a recent review concluded that nowadays, considerable dose reductions in spinal CT for various indications can be realized with dose reductions around 50% 43 . Although some novel approaches during image acquisitions have not yet been implemented in commercially available MDCT systems (e.g., sparse sampling), such techniques may become of general interest in the near future 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies regarding the application of new reconstruction algorithms to spinal CT, have focused on the depiction of high-contrast structures, improving the visualization of the Adamkiewicz artery on CT angiography 6,7 and reducing the radiation dose without compromising the visualization of bone. 16 Recently, studies on the application of DLR for evaluating degenerative changes in the cervical 17 or lumbar 18 spine on unenhanced CT have been published. According to them, noise reduction due to DLR improved visualization of structures in the spinal canal region, which helped improve the interobserver agreement (.739 and .794 for the cervical and lumbar spine, respectively) for the evaluation of spinal canal stenosis due to bulging disc/ degenerative changes compared to hybrid-IR (.704 and .732 for the cervical and lumbar spine, respectively).…”
Section: Discussionmentioning
confidence: 99%